A New Hybrid Power Configuration In HEV and Its Driving BLDC Development - Yanliang Xu Yanliang Xu; Changfeng Li Changfeng Li (Universitas Ahmad Dahlan, 2013)
Hybrid electric vehicle (HEV) that has the advantages of high performance, high fuel efficiency, low emission, and long operating range is focused on nowadays. A new hybrid power configuration used in HEV is presented with different control strategies and HEV performances when equipping different weight of fuel power and battery one. In order to realize the new hybrid power configuration especially in the refitted HEV, fractional-slot concentrated-winding BLDC with higher rated spinning speed is given and the prototyped one is developed and fabricated which satisfies successfully the requirements of high performance and demission restriction for the refitted HEV.